Когда цветут эдельвейсы: повести / Владимир Топилин - Топилин Владимир Степанович (Сибириада, 2022)
Экземпляры: 3 (20240507) / Инвентарный номер: 57230 / Цена: 511.86 / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Т 58 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-44